Server Virtualization Technology: A proposed Implementation Model - Obegi, Felix; Raburu, George; Okoya, Michael (IISTE, 2019)
The study sought to fill the existing gap on issues surrounding the implementation of Server virtualization technology, which have received relatively little attention. The study investigated the implementation of server virtualization technology by companies listed in the Nairobi Securities Exchange. It employed a correlational research design and targeted the IT and Operations departments of listed companies on the NSE. The target population consisted of 120 persons, and the study used a census method. Primary data was collected through use of questionnaires. Data collected was sorted, coded and input into the statistical package for social sciences (SPSS) version 21.0 for production of graphs, tables, descriptive statistics and inferential statistics. Correlation analysis revealed that environmental factors, technological factors, organizational factors and human factors had a positive and significant association with server virtualization implementation.